Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen (Studi pada Konsumen “Warung Bek Mu 2” Banjaranyar Paciran Lamongan) - Ahmad Afan Zaini (Al-Maqashid: Journal of Economics and Islamic Business, 2022)
This study aims to clarify and determine the influence of service quality on customer satisfaction together and partial as well as to determine which variable is dominant influence on customer satisfaction at “Warung Bek Mu 2” Nasi Pecel Khas Lamongan Pantura. The indicators of independent variable used in this study are tangible, reliability, responsiveness, assurance and empathy and dependent variable in this study is the customer satisfaction. This research was conducted at “Warung Bek Mu 2” Nasi Pecel Khas Lamongan Pantura. The population sample used is customers at “Warung Bek Mu 2” Nasi Pecel Khas Lamongan Pantura. The sampling technique used Accidental Sampling. The sample used in this study amounted to 100 people respondents. Based on the F test results was showed that F Sig. 0.000<0.005, which means the indicators of Service Quality Variable which consists of tangible, reliability, responsiveness, assurance and empathy have a significant influence on the customer satisfaction. Based on the t results showed that the indicators of Service Quality variable which consists of tangible, reliability, responsiveness, assurance and empathy significantly influence on the customer satisfaction. T test results also showed that the responsiveness indicator (X3) variable have had the most powerful effect compared with other indicators variable, so the responsiveness (X3) variable have the dominant influence on the customer satisfaction.